Farmacoeconomia dei COXIB nella patologia osteoarticolare: revisione della letteratura - Russo, Pierluigi; Degli Esposti, Luca; Capone, Alessandro; Degli Esposti, Ezio; Caprino, Luciano (Farmeconomia. Health Economics and Therapeutic Pathways, 2003)
A new class of anti-inflammatory agents, the selective inhibitors of cyclooxygenase-2 (COXIBs), has been recently introduced into the market for the treatment of osteoarthritis and reumatoid arthritis. Randomized and controlled clinical trials showed a similar efficacy and a better tolerability profile of COXIBs compared with conventional non-steroidal anti-inflammatory drugs (NSAIDs). The aim of this study was to perform a scientific literature review relating to the economic impact produced by COXIBs’ introduction. The research of references included the following databases: MEDLINE, EMBASE and the NHS (Economic Evaluation Database) of the York University. A total of 67 in extenso pubblications have been extracted. Of these 13 papers having the specific objective to evaluate the economic implications of COXIBs in comparison to conventional NSAIDs was analysed. In ten cases (77%), cost-effectiveness analyses were performed. The European context was considered in eight cases (62%), while that of North America and Asia were investigated in four and one case, respectively. The analysis of costs took always into account direct costs of the management of arthritis exclusively (drugs, and resources associated with the treatment of gastrointestinal side effects). Indirect and intangible costs were never considered. The results of this review highlight that the higher tollerability profile of COXIBs may generate a cost-saving. This cost-saving seems to be basically due to the reduced frequency of gastroprotective agents coprescription and also to a lesser appearance of severe gastrointestinal side effects compared with conventional NSAIDs. Besides the disease management improving, the cost-saving associated with COXIBs can completely or partially offset the net increase of expense induced by their higher price of purchase.